Kualitas Benih Selama Perkembangan Biji Kacang Hijau Dengan Pemberian Fosfat - Elza Zuhry; Islan ' (Universitas Riau, 2007)
The development of mungbean seed is affected by the seed filling process. The objective of this research was to know the effect of phosphate dosage toward quality of mungbeen seed during its development within harvesting time (15, 20, 25, and 30 days after flowering). The research was carried out in Agricultural Experiment Station, University of Riau and Seed Test was carried out in Plant Breeder Laboratory which lasted for three months (September-November 2006). This research used Complete Randomized Block Design with four treatments and three replications and Duncan New Multiple Range Test (5%). The treatments were P1=80 kg TSP/ha, P2=90 kg TSP/ha, P3=100 kg TSP/ha, P4=110 kg TSP/ha. Parameters measured were index value test, first count test, standard germination test, and root and shoot growth test at harvest age of 15, 20, 25, and 30 days after flowering. The application of phosphate of 100 kg TSP/ha provided the best result for quality of mungbeen seed. Key Words : mungbeen, viability, vigor, seed quality